PENGARUH INVESTMENT OPPORTUNITY SET, DEBT TO EQUITY RATIO, GROWTH, EARNINGS PER SHARE, TOTAL ASSETS TURNOVER TERHADAP DIVIDEND PAYOUT RATIO (Pada Perusahaan Manufaktur Go Public di BEI Periode 2011-2013) - Dewi Sampurna, Cynthia; Widyarti, Endang Tri (Faculty of Economics and Business Diponegoro University, 2015)
This study is performed to examine the effect of Investment Opportunity Set (IOS), Debt to Equity Ratio (DER), Growth, Earning per Share (EPS), Total Asset Turnover (TAT) toward Dividend Payout Ratio (DPR) in manufacture companies that is listed in Indonesian Stock Exchange over period 2011-2013.The population of this research is 148 manufacture companies that listed in Indonesian Stock Exchange period 2011-2013. Sampling technique used here is method of purposive sampling. The data is obtained based on Indonesia Stock Exchange (IDX) 2011-2013 publication. It is gained sample amount of 30 manufacture companies from 148 manufacture companies those are listed in Indonesia Stock Exchange. The analysis technique used here is multiple regression with the last square difference and hypothesis test using f-statistic to examine the mean of mutual effect with level of significance 5% and t-statistic to examine partial regression coefficient. In addition, classical assumption is also performed including normality test, multicolinearity test, heteroscedasticity test, and autocorrelation.Regression equation is DPR= 0,006 + 0,005 IOS – 0,073 DER – 0,034 GROWTH + 0,033 Ln,EPS 0,192 TATO + e. According to analysis indicates that IOS, EPS and TATO has a significant positive influence on Dividend Payout Ratio. DER and Growth has negative influence on Dividend Payout Ratio. Predictable of the five independent variables toward Dividend Payout Ratio (DPR) is 26,8% as indicated by adjust R square that is 26,8% while the rest 73,2% is affected from other factors outside of this study model.